PERANCANGAN PROYEK BOUTIQUE HOTEL DENGAN PENDALAMAN SENSE OF PLACE OLEH KONSULTAN ARSITEKTUR INTERIOR JENEE STUDIO - Jennifer Natalie; Astrid Kusumowidagdo (Universitas Ciputra Surabaya, 2023)
The design process of interior architecture consultant Jenee Studio, which focuses on the approach to a sense of place as well as architectural and interior design plans for a boutique hotel on Gili Trawangan Island, Lombok, is contained in the final assignment report, “Project Design Boutique Hotel With Insight Sense of Place By Interior Architecture ConsultantJenee Studio.” Approach a sense of place is made to lift problems from socio-cultural trends related to demographics and tourism development in Indonesia. It’s intended that by employing the sense of place method, it will be possible to create pieces that stand out and offer users a fresh experience in addition to highlighting the conventional component of interior architecture. This project design was created to fulfill the final assignment for the Ciputra University Department of Interior Architecture and to be the first portfolio for Jenee Studio to handle real projects. This site was formerly an undeveloped property that was to be the site of a boutique hotel with effective circulation and traditional Lombok features in its interior design and ambiance. The design method uses an approaching sense of place which will impact the design in general. The research method used is qualitative by observing the physical elements of the potential site. It is hoped that the results of this research will be a descriptive sense of place through the elaboration of physical and social elements in the interior design of boutique hotels.